Detection of a Low Level and Heterogeneous B Cell Immune Response in Peripheral Blood of Acute Borreliosis Patients With High Throughput Sequencing - Kirpach, Josiane; Colone, Alessia; Bürckert, Jean-Philippe; Faison, William J.; Dubois, Axel R. S. X.; Sinner, Regina; Reye, Anna L.; Muller, Claude P. (Frontiers in Immunology, 2019)
The molecular diagnosis of acute Borreliosis is complicated and better strategies to improve the diagnostic processes are warranted. High Throughput Sequencing (HTS) of human B cell repertoires after e.g., Dengue virus infection or influenza vaccination revealed antigen-associated “CDR3 signatures” which may have the potential to support diagnosis in infectious diseases. The human B cell immune response to Borrelia burgdorferi sensu lato—the causative agent of Borreliosis—has mainly been studied at the antibody level, while less attention has been given to the cellular part of the humoral immune response. There are indications that Borrelia actively influence the B cell immune response and that it is therefore not directly comparable to responses induced by other infections. The main goal of this study was to identify B cell features that could be used to support diagnosis of Borreliosis. Therefore, we characterized the B cell immune response in these patients by combining multicolor flow cytometry, single Borrelia-reactive B cell receptor (BCR) sequencing, and B cell repertoire deep sequencing. Our phenotyping experiments showed, that there is no significant difference between B cell subpopulations of acute Borreliosis patients and controls. BCR sequences from individual epitope-reactive B cells had little in common between each other. HTS showed, however, a higher complementarity determining region 3 (CDR3) amino acid (aa) sequence overlap between samples from different timepoints in patients as compared to controls. This indicates, that HTS is sensitive enough to detect ongoing B cell immune responses in these patients. Although each individual's repertoire was dominated by rather unique clones, clustering of bulk BCR repertoire sequences revealed a higher overlap of IgG BCR repertoire sequences between acute patients than controls. Even if we have identified a few Borrelia-associated CDR3aa sequences, they seem to be rather unique for each patient and therefore not suitable as biomarkers.